Food and health: a vision from the curricular design of the Bachelor of Food Sciences - Guardado Yordi, Estela (2019)
The training of professionals to obtain a Bachelor´s Degree in Food Science requires the development of biomedical science information management skills. This study proposes the curriculum design of an elective course and its integration with the Information and Communication Technologies (ICT). This design was developed based on the professional model and includes the concept of curriculum integration of ICT expressed in a curriculum planning, so that its use responded to educational needs and demands. The programs Wordpress and eXeLearning were used for the preparation of the materials in Web format and the elaboration of Edublog. Conclusions: The designed and implemented resources form a system of integrated means and are comprised of chapters in electronic format, a web course, an Edublog and a monographic product on the impact of sugar consumption on health. Motivation, management and evaluation of scientific information were achieved.